Yi–Qi–Jian–Pi–Xiao–Yu–Xie–Zhuo Formula Improves Muscle Atrophy via Modulating the IGF-1/PI3K/Akt Signaling Pathway in 5/6 Nephrectomized Rats - Xia, Hong; Zhang, Bingbing; Yang, Dan; Zhu, Chengyue; Zhang, Jiudan; Chen, Hongbo; Ma, Hongzhen; Hu, Shouci; Xu, Chao; Shi, Chengqian; Lu, Keda; Zhang, Peipei (Frontiers in Pharmacology, 2021)
The Yi–Qi–Jian–Pi–Xiao–Yu–Xie–Zhuo (YQJPXYXZ) formula has been used for treating chronic kidney disease (CKD) for many years with good efficiency based on the cumulative empirical experience of previous practitioners. Impairment of the IGF-1/PI3K/Akt signaling pathway plays an important role in mediating muscle wasting. This study aimed to observe effects of the YQJPXYXZ formula on muscle atrophy in CKD rats and investigate its possible mechanism on regulation of the IGF-1/PI3K/Akt signaling pathway. The 5/6 nephrectomized rats were randomly allocated into 3 groups: the CKD group, the KT (compound α-ketoacid tablets) group, and the YQJPXYXZ group. Besides, sham-operated rats were included as the sham group. All rats were treated for 12 weeks. Results showed that administration of the YQJPXYXZ formula prevented body weight loss and muscle fiber size decrease. Moreover, the YQJPXYXZ formula increased the IGF-1 level of serum and skeletal muscle in CKD rats and enhanced the phosphorylation level of Akt. Furthermore, the YQJPXYXZ formula decreased the Atrogin1 and MuRF1 mRNA and MuRF1 proteins. In conclusion, our data demonstrated that the YQJPXYXZ formula improves muscle wasting in CKD rats, which might be associated with the modulation of the IGF-1/PI3K/Akt signaling pathway and inhibition of the ubiquitin–proteasome system (UPS).